Is there a disc in the superluminal quasars? - Rokaki, E.; Lawrence, A.; Economou, F.; Mastichiadis, A. (Monthly Notices of the Royal Astronomical Society, 2003)
We look for the expected signature of an accretion disc by examining the properties of the Hα emission line versus viewing angle in a sample of 22 superluminal (SL) quasars. The Doppler factor δ, jet velocity γ and viewing angle θ towards the jet are derived from published radio and X-ray data. Most of the Hα spectra (14) have been observed at the United Kingdom Infrared Telescope (UKIRT) and are reported here. About a quarter of the SL objects have weak or absent Hα emission lines, with small equivalent widths (EW). These have high optical polarization, radio core dominance and Doppler factor, and most of them have high apparent SL velocity and low viewing angles. Therefore these weak-EW objects almost certainly have relativistically beamed optical continua. The strong-EW objects also show a clear beaming effect, but a much weaker one, with line EW varying by only a factor of 3 while radio core dominance varies by a factor of several hundred. The correlation of EW with θ is quantitatively in good agreement with the prediction of a flat accretion disc with limb darkening. The weak- and strong-EW sources also show an anticorrelation of line velocity width with the various beaming indicators. Again, the correlation with the derived viewing angle θ shows a quantitative agreement with the effect expected for an axisymmetric structure with velocity dominated by rotation. The line emission cannot come from the surface of the disc, or the line beaming would cancel the continuum beaming. However, it could come from an axisymmetric system of clouds corotating with the accretion disc.
Keywords: Accretion; accretion discs; Astrophysics; galaxies: active; quasars: emission lines; quasars: general; radio continuum: galaxies